Emerging trends in precision medicine and its impact in pharmacy practice - Krishna, Abhishek S.; Nair, Harikrishnan V.; Dharan, Shaiju S.; Nair, Keerthi G. S. (International Journal of Basic & Clinical Pharmacology, 2024)
Precision medicine is revolutionizing healthcare by tailoring treatments to an individual’s unique genetic makeup, life style, and environment. This abstract explores the latest trends in precision medicine and discusses how it impacts pharmacy practice, including the development of targeted therapies and the role of pharmacogenomics in optimizing drug selection and dosage. Exciting advancements in this field offer the potential for improved patient outcomes and more precise medication management.